Use of friedewald equation for dyslipidemia in metabolic syndrome - Kaur, Jaspinder (International Journal of Medicine, 2014)
Objective: The Friedewald equation is frequently used to estimate low-density lipoprotein cholesterol (LDL-C) in routine patient care; however, recently many limitations have emerged regarding its use. Aim: Analyse the use of Friedewald equation for dyslipidemia in metabolic syndrome. Methods: Subjects were selected with metabolic syndrome that fulfilled consensus statement for Asians Indians and excluded those with triglyceride (TG) ?400mg/dl, and chronic liver and/or kidney disease. Total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), TGs, and LDL-C were measured with direct assays. LDL-C was further estimated using the equation and compared with LDL-C by direct assay. Results: The mean and standard deviation of TC, TGs, HDL-C, and LDL-C were 194.77±24.38mg/dl, 174.84±60.27mg/dl (p<0.0001), 40.68±5.40mg/dl (p<0.05), and 122.30±19.30mg/dl among subjects with metabolic syndrome. On the other hand, Friedewald estimated LDL-C and VLDL-C were 121.29±18.84mg/dl and 35.08±12.65mg/dl (p<0.0001). Furthermore, a statistically significant higher TGs/HDL-C (p<0.0001) and LDL-C/HDL-C ratios was observed in subjects with metabolic syndrome. However, no significant difference was recorded between the two methods of estimating LDL-C. Conclusion: TGs/HDL-C was found significantly higher among subjects with metabolic syndrome; however, no significant difference between both Friedewald equation and direct measurement method for LDL-C estimation was observed. Hence, the accuracy of LDL-C estimation formulas and direct methods for measurement in patients with the metabolic syndrome requires further exploration. Keywords: Dyslipidemia, Friedewald Equation, Metabolic Syndrome.